Ossifying fibromyxoid tumours with lipomatous and cartilaginous differentiation: A diagnostic pitfall - Klubíčková, Natálie; Billings, Steven; Dermawan, Josephine K T; Molligan, Jeremy F; Fritchie, Karen (Histopathology, 2025)
AIMS: Ossifying fibromyxoid tumour is a rare mesenchymal neoplasm predominantly affecting adults characterised by a multinodular growth pattern and the presence of a fibrous pseudocapsule with areas of ossification. Prompted by the recognition of a non-ossifying ossifying fibromyxoid tumour with lipomatous differentiation which caused diagnostic difficulty, we sought to further explore cases of ossifying fibromyxoid tumour with non-osseous heterologous elements. METHODS AND RESULTS: A search of our institutional and consultation archives revealed three additional cases that demonstrated lipomatous components and two cases with cartilaginous differentiation. RNA-sequencing revealed fusions involving PHF1 (n = 4) or EPC1 (n = 1) in all (five of five) cases tested, including EPC1::PHC1 and JAZF1::PHF1 fusions, which have not been reported before in ossifying fibromyxoid tumour. CONCLUSION: These six cases expand the histomorphological spectrum of ossifying fibromyxoid tumour, introducing lipomatous differentiation as a hitherto undocumented feature. Awareness of these rare variants will ensure appropriate diagnosis and clinical management.
Keywords: Female; lidé středního věku; buněčná diferenciace; Fibroma, Ossifying; nádory měkkých tkání; chrupavka; Lipoma; mužské pohlaví; chondroid differentiation; lipoblasts; soft tissues; Humans; dospělí; Cartilage; ossifying fibromyxoid tumour; osifikující kostní fibrom; Cell Differentiation; lipom; lidé; Middle Aged; cartilaginous differentiation; Diagnosis, Differential; senioři; OFMT; Soft Tissue Neoplasms; diferenciální diagnóza; ženské pohlaví; Aged; Adult; lipomatous differentiation; Male